2006
DOI: 10.1111/j.1365-2842.2005.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with symptoms of temporomandibular disorders in a population of 50‐ and 60‐year‐old subjects

Abstract: The aims of this study were first to investigate, by means of a mail questionnaire, variables from three domains: (i) socio-economic attributes; (ii) general and oral health; and (iii) dental attitudes and behaviours in a large sample of 50- and 60-year-old subjects, and second to compare subjects with or without reported temporomandibular joint (TMJ) pain with respect to these variables. In 2002, a questionnaire was mailed to all 50- and 60-year-old subjects in two Swedish counties, Orebro and Ostergötland (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
112
2
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 16 publications
24
112
2
15
Order By: Relevance
“…36 We believe that inattention to sex differences may contribute to the lack of consensus concerning the clinical usefulness of the pain drawing. Supporting our belief is that sex differences exist in the incidence of specific chronic pain conditions 12,17,19,21,43,56,58 and in the response to experimental pain stimuli. 10,16 Furthermore, pain studies have demonstrated sex differences in physiological response to pain, 59 central processing of pain, 15 as well as psychological factors like coping style, 10,20,39 anxiety, 14,34 and socialization.…”
supporting
confidence: 52%
“…36 We believe that inattention to sex differences may contribute to the lack of consensus concerning the clinical usefulness of the pain drawing. Supporting our belief is that sex differences exist in the incidence of specific chronic pain conditions 12,17,19,21,43,56,58 and in the response to experimental pain stimuli. 10,16 Furthermore, pain studies have demonstrated sex differences in physiological response to pain, 59 central processing of pain, 15 as well as psychological factors like coping style, 10,20,39 anxiety, 14,34 and socialization.…”
supporting
confidence: 52%
“…The adjusted risk ratio for tinnitus among subjects with TMD diagnosis and headache was 4.52 (95% CI: 1.67, 12.19; p = .0002) higher than in subjects with only TMD diagnosis (RR=3.8) or only headaches (RR=1. 4) Similarly, the adjusted risk ratio for tinnitus among subjects with an MPD diagnosis and headaches was 3.59 (95%CI: 1.82, 7.06) higher than in subjects with only MPD diagnosis (RR=3.02) and only headaches (RR= 1.75) CONCLUSION: These findings suggest higher rate of tinnitus among subjects with MPD than other forms of TMD. Moreover, the risk for tinnitus is six times higher if subject has TMD diagnosis and headache and three times higher in myofascial group with headaches.…”
mentioning
confidence: 57%
“…In Japan, the National Survey of Dental Disease conducted in 2011 showed that the percentage of individuals (age, ≥15 years) with TMJ sounds was approximately 15% in men and 17% in women, while the percentage of those with TMJ pain was 2 and 4%, respectively (21). Several studies performed in various countries have found that women have more TMD problems than men (22)(23)(24). Although a significant difference for total percentage was not observed between the two genders in Japan, women aged 25-29 years exhibited the highest prevalence of TMJ sounds and pain as compared to the other age groups (21).…”
Section: Prevalence Of Tmd In General Populationmentioning
confidence: 99%